Comparisons of multi-wavelength oscillations using sagnac loop mirror and mach-zehnder interferometer for ytterbium doped fiber lasers - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Shahi, S.; Lim, K.S.; Ahmad, Harith (IOP Publishing, 2010)
A multiwavelength Ytterbium-doped fiber ring laser operating at 1030 nm region is demonstrated using a Sagnac loop mirror and a Mach-Zehnder interferometer. We report the Performance comparisons of multi-wavelength oscillations in Yb(3+) doped fiber lasers (YDFL) with typical commercial ytterbium doped silica fibers. By adjusting the polarization controller (PC), a widely tunable laser range of 22 nm from 1030 nm to 1050 nm is obtained. The Mach-Zehnder interferometer (MZI) design has exhibited simplicity in the operation for controlling the smallest wavelength spacing compared to Sagnac loop mirror method. In our observations, the smallest achieved stable wavelength spacing in Sagnac loop mirror setup and MZI setup were 2.1 nm and 0.7 nm, respectively. In case of nine-wavelength operation with a MZI setup, the stability, Full Width at Half Maximum (FWHM) and side mode suppression ratio (SMSR) of laser lines are not affected by increasing pump power, While for above four wavelength operation, the laser stability with Sagnac loop mirror becomes worse specially for higher input pump power and the power fluctuation among the wave-lengths would be also slightly larger.